PHYSICAL, SEXUAL AND PSYCHOLOGICAL VIOLENCE ACCORDING TO RODGERS’ EVOLUTIONARY CONCEPTUAL ANALYSIS - Bonamigo, Victoria Grassi; Torres, Fernanda Broering Gomes; Lourenço, Rafaela Gessner; Cubas, Marcia Regina (Cogitare Enfermagem, 2022)
Objective: to clarify the concepts of physical, psychological, and sexual violence and, from the results obtained, to compare similarities and differences among concepts, their characteristics, conditions for events, and possible outcomes. Methods: Rodgers’ evolving concept analysis was used. The antecedents, attributes and consequents were extracted from 91 documents published in 2018, in Portuguese, English, French or Spanish, by search using the descriptors “physical violence”, “psychological violence” and “sexual violence”. Results: for “physical violence” 17 attributes, one antecedent and seven consequents were extracted; for “sexual violence” 31 attributes, 10 antecedents and two consequents; and for “psychological violence” 33 attributes, four antecedents and six consequents. Final considerations: different types of violence have different acts that characterize them, and that when (re)known by the nurse, allow for an optimized and quality care planning.